Distinctive Features of Extracellular Vesicles Present in the Gastric Juice of Patients with Gastric Cancer and Healthy Subjects - Skryabin, Gleb; Enikeev, Adel; Beliaeva, Anastasiia; Galetsky, Sergey; Bagrov, Dmitry; Moiseenko, Andrey; Vnukova, Anna; Imaraliev, Oiatiddin; Karasev, Ivan; Tchevkina, Elena (International journal of molecular sciences, 2025)
Extracellular vesicles (EVs) are key mediators of intercellular communication and play a vital role in cancer progression. While EVs in the blood are well-studied, those in local body fluids, such as gastric juice (GJ), remain underinvestigated. Previously, we first characterized GJ-derived EVs and demonstrated their potential for gastric cancer (GC) screening. Here, we conducted a detailed morphological analysis of GJ-EVs using cryo-electron microscopy, identifying both typical and atypical EV subtypes, and categorized their relative abundances. A subsequent comparison of the size distribution of GJ-derived EVs by nanoparticle tracking analysis revealed significant differences between samples obtained from GC patients (n = 40) and healthy subjects (n = 25). Additionally, the mean EV sizes differed significantly according to the presence of the tetraspanin protein CD9. Furthermore, the ratio of CD9-positive to CD9-negative EV samples differed between cancer patients and healthy donors. These data suggest that GJ contains distinct subpopulations of EVs that vary in size and CD9 expression, as well as EVs with certain types of atypical morphology. The identification of discrepancies in EV size and the presence of CD9 between GJ from cancer patients and healthy individuals offers potential avenues for the identification of new GC markers.